BIODIVERSITY AND POPULATION STRUCTURE OF INDIGENOUS BREEDS OF SHEEP IN NIGERIA (2014)
Genetic characterisation is the basis for selective breeding, crossbreeding, conservation, utilisation, improvement and rational management of animal genetic resources. Indiscriminate crossbreeding has led to erosion of genetic resources of indigenous domestic animals in Nigeria. Information on the genetic biodiversity of the indigenous sheep in Nigeria has not been adequately documented. Therefore, the population structure and biodiversity of indigenous breeds of sheep in Nigeria were assessed in this study. Twenty-five sheep each of Balami, Uda, Yankassa and West African Dwarf (WAD) breeds were purposively sampled from Lokoja, Iwo, Okene and Ibadan for biochemical studies. Blood (5 mL) samples were collected to determine variations at four structural protein loci: Albumin (Alb), Transferrin (Tf), Carbonic Anhydrase (CA) and Haemoglobin (Hb), using cellulose acetate electrophoresis. Blood (5 mL) from 24 Balami, 25 Uda, 23 Yankassa and 19 WAD sheep were sampled from Shika, Guga and Ibadan for microsatellite loci analysis. Using real time PCR, 13 microsatellite marker loci: CSRD247, HSC, INRA63, MAF214, OARAE129, OARCP49, OARFCB304, BMS4008, D5S2, OARFCB20, MAF65, MCM527, and SPS113 were genotyped. The populations were characterised for genetic variability using Mean Number of Alleles (MNA), allele frequencies, Number of Unique Alleles (NUA), Polymorphic Information Content (PIC), observed Heterozygosity (Ho), genetic distance (D). Data were analysed using F-statistic (Fit, Fis, Fst), Analysis of molecular variance, cluster analysis and test of Hardy-Weinberg Equilibrium (HWE) at α0.05. Thirteen allelic variants (HbA, HbB, CAF, CAS, AlbA, AlbB, TfA, TfB, TfC, Tf D, TfE, TfG and TfP) were observed at the four protein loci. Modal number (seven) occurrence of alleles was at the Tf locus while two were observed in other loci. The Ho were 0.52, 0.59, 0.61 and 0.52 for Balami, Yankassa, WAD and Uda respectively. The closest D (0.05) was between Balami and Yankassa, while between Balami and WAD was farthest (0.44). Homozygote deficiency (Fis = -0.25; Fit = -0.05) was observed within breeds. Significant HWE were observed in Yankassa (Hb and Tf) and WAD (CA). A total of 149 alleles were observed at the microsatellite loci. The MNA per locus was 11.4±4.0 and ranged between 5.9±2.3 and 8.5±3.4 among breeds with NUA of 45. The PIC observed across loci was 0.65, while the Ho ranged from 0.63 (Balami) to 0.69 (Uda). The D was least (0.09) between Balami and Uda, and highest (0.31) between WAD and Uda. Observed inbreeding within populations (Fis = 0.05) resulted in heterozygote deficiency and low genetic differentiation among breeds (Fst = 0.06). Only 4.5% of the total genetic variation was explained by population differences, 2.6% by variation within population and 92.9% by differences among individuals. Yankassa clustered with Balami at protein loci, while Balami and Uda clustered at microsatellite loci. The HWE was significant for BMS4008, CSRD247, HSC, INRA63, MAF65, MAF214, MCM527, OARAE129, OARCP49 and OARFCB304 microsatellite loci in at least one population. Genetic exchange was present at biochemical loci, whereas breed homogeneity was supported at microsatellite loci. Selection and crossbreeding between West African dwarf sheep and any of Uda, Balami or Yankassa will improve breed crosses